DEVELOPING LATHES POSTPROCESSOR GENERATING CYCLES OF PROCESSING GROOVES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
This article explores the possibility of developing a post-processor generating circles for radial and facsimile grooves in PTC Creo environments using a generalized postprocessor G-POST and a specialized language FIL (Factory Interface Language). The proposed development approach can also be applied to post-processor generating cycles for rough and fine turning (G71, G72 and G70).